ANALISIS EFISIENSI USAHA MIKRO KECIL MENENGAH GULA MERAH DI DESA SUMBERINGIN KECAMATAN SANANKULON KABUPATEN BLITAR - Aghnia Ramadani; Arfida BR (Program Studi Ekonomi Pembangunan, 2017)
efficiency analysis on small and medium businesses in Sumberingin village Sanankulon district Blitar town. There are many food processing industry in the for UMKM (Small And Medium Businesses) can be found in Sumberingin Village such as brown sugar processing UMKM wich keep on growing due to high demand. The objectives of this research are to obtain the profile of brown sugar UMKM in the are, to find out the figure of sales, to count BEPs and to analize the businesses efficiency of the UMKM. The total set of observation (population) in this research is all the UMKM currently resids in the area. A total of 168 unit according to BPS Blitar Town in 2015. Data was analyzed by counting the number of total production cost, number of sales, net sales, BEP (Break Even Point) and efficiency analysis. The result of this research shows that, the brown sugar UMKM in the area is managed efficiently and very potential to be expanded by the Local Government (Pemkab Blitar) so that they will be able to compete in the local, national, and international market. The brown sugar UMKM in the area can surely be a potential business for the people to make ends meet.Keyword : Brown Sugar UMKM, Efficiency Analysis, Number Of Sales